Introduction of Hindered Electrophiles via C–H Functionalization in a Palladium-Catalyzed Multicomponent Domino Reaction - Qureshi, Zafar; Schlundt, Waldemar; Lautens, Mark (Synthesis, 2015)
A general method for the incorporation of secondary alkyl iodides in a palladium-catalyzed multicomponent domino reaction is reported. With the relatively inexpensive Pd(OAc)2 as the catalyst and norbornene as a mediator, a variety of 1,2,3-trisubstituted aromatic compounds were synthesized. The reaction was shown to be scalable, producing excellent isolated yields on up to 5 mmol scale. Chiral alkyl iodides were also incorporated without any loss of stereochemical information. The developed method offers an expedient and mild C–H functionalization strategy for the synthesis of sterically congested aromatic compounds in a one-pot process.
Keywords: multicomponent reaction; palladium; Catellani reaction; domino reaction; C–H functionalization